NATURAL RUBBER MODIFICATION FOR UPPER LAYER OF RUBBERIZED ASPHALT PAVING BLOCK AS SHOCK ABSORBER - Nasruddin Nasruddin (Jurnal Dinamika Penelitian Industri, 2017)
The research of rubber compounding modification for upper layer of rubberized asphalt paving block as shock absorber using natural rubber, styrene butadiene rubber (SBR) as synthetic rubber, fly ash as filler and also vegetable oil as plasticizer has been conducted. The research design was varying the filler Si-69, fly ash and palm oil. The five formulas A, B, C, D, and E designed by varying the amount of Si-69 (48.5; 50.75; 53.00; 55.25; and 57.50) phr; coal fly ash (4.75, 7.00, 9.25, 11.50 and 13.75) phr; and vegetable oil from palm oil (6.5, 7.0, 7.5, 8.0, 8.5, and 9) phr, while the NR:SBR was 82.50: 17.50 phr for each formula. Based on the testing results, the formula D has the best physic-mechanical properties among others. It has specific gravity 1.78 g/cm3; hardness 81 ShoreA; abrasion resistance 52,85 mm3 ; compression set, 25% defl, 70oC, 22h: 21,40%; tensile strength 195,69 N/ m3; ozone resistance showed no crack.